Cognition of feedback loops in a fire-prone social-ecological system. (May 2022) - Hamilton, Matthew; Salerno, Jonathan; Fischer, Alexandra Paige
Highlights: Complex social-ecological feedback loops challenge wildfire risk governance. We evaluate cognition of feedback loops using cognitive maps from diverse stakeholders. The prominence of feedback loops increases with aggregation of cognitive maps. Stakeholders are more likely to perceive amplifying and desirable feedback loops. Abstract: Increasing wildfire severity highlights the need for large-scale shifts in management of fire-prone landscapes. While prior research has focused on cognitive biases, social norms, and institutional disincentives that limit reform, such factors are best understood as components of feedback loops that operate within complex adaptive systems. We evaluated the prominence and function of feedback loops embedded in cognitive maps—beliefs about patterns of causal relationships that drive system dynamics—elicited from a diverse cross-section of stakeholders in a fire-prone region in the U.S. West. We demonstrate that cognition of feedback loops is rare among individuals, but increasingly prominent within aggregations of cognitive maps, which underscores the importance of collaborative decision-making. Our analysis further reveals a bias toward perception of amplifying feedback loops and of loops in which management actions result in desirable outcomes, which points to areas where progress may be made in reforming wildfire risk governance.